Agentes patógenos que afectan la cría de abejas melíferas (Apis mellifera): Ascosphaera apis, Paenibacillus larvae, Melissococcus plutonius - Guerrero Cárdenas, Andrés Felipe; Rosas Martínez, Ivonne Catherine (Universidad Antonio Nariño, 2022)
Infections by A. apis, P. larvae and M. plutonium have a significant impact on Apis mellifera communities from both an environmental and economic point of view. Ascosphaera apis, widespread globally, causes ascospherosis, also known as chalk disease, an invasive mycosis that affects developing larvae. Environmental conditions such as humidity and temperature influence the spread of infection. Virulence is associated with the type of mating and genetic factors of both the fungus and the host bee. P. larvae and M. plutonium infect bee larvae, and the pathogenic activity of these bacteria is very intense, leading to the destruction of the colonies. The spread of the infection is influenced by the behavior of the bees within the hive. Although the mechanisms through which these pathogenic agents exert their action are well established, adequate diagnostic procedures at the apiary level are not yet well implemented. It is necessary to establish routine protocols for early diagnosis based on molecular biology techniques to prevent these infections from developing. Advances in molecular biology will allow the identification and distribution of both fungal and bacterial strains in the short term, which will allow better sanitary control of apiaries and will provide more information on the behavior of these bacteria in terms of adaptation to different habitats as well as resistance and susceptibility to antibiotics.